AN ELECTRONIC DICTIONARY: A MEDIA TO TEACHSTUDENTS' PRONUNCIATION :A Pre-Experimental Study of Eleventh Grade Students at a Vocational Schoolin Bandung - Raidah Zahra, - (2015)
Most Indonesian students have difficulties in learning pronunciation through Monolingual Dictionaries. Therefore, this research aims to investigate the effectiveness of the use Electronic Dictionary media in improving students' pronunciation and to discover students' opinions towards the use of the media in their English class.The study implemented a pre-experimental design. The sample involved 33 students of the 11th grade students at one state vocational school in Bandung. The sample was given Electronic Dictionary media treatment that was adopted from Hillary (1999, p. 830). The data of this study were obtained through pre-test, post-test, and questionnaires. The pre-test and post-test were given in form of pronunciation test. The data from pre-test and post-test were analyzed statistically using SPSS 21. The result showed that the value of the tobtained > 1<:ritical consequently the null hyphothesis was rejected. It means that the use of Electronic Dictionary media gave an influence towards the improvement of students' pronunciation. Data from questionnairesresults showed that nearly all of students (96.35%) gave positive opinions towards the implementation of the media and a few students (3.65%) gave negative opinions towards the media. Therefore, Electronic Dictionary is recommended to be implemented in teaching pronunciation.